2020
DOI: 10.1002/dac.4369
|View full text |Cite
|
Sign up to set email alerts
|

Secure image transmission through crypto‐OFDM system using Rubik's cube algorithm over an AWGN channel

Abstract: Summary Confidentiality of information must be maintained when it is required to be transmitted over a communication channel or when it is stored in a computer for further information access. Establishing a highly reliable and secure means of wireless communication for the transfer of digital data (text, images, audio, and video) from source to destination is becoming a prime requirement in present‐day wireless communications. Security can be achieved at the network level as well as at the data level. Data‐lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This table shows that compared to systems employed in past studies, the NPCR and UACI values of the suggested systems in this paper are considered good values to avoid UACI and NPCR attacks and have a better image transmission that is more efficient and safer. (12) 𝑃𝑃 𝑟𝑟 (𝑋𝑋 = 𝜒𝜒 𝑗𝑗 ) = 1 𝐼𝐼𝐼𝐼 (13) where X is the original image, Pr(𝜒𝜒 𝑗𝑗 ) 𝑖𝑖𝑖𝑖 𝑒𝑒𝑞𝑞 (13) is the probability of X = 𝜒𝜒 𝑗𝑗 , 𝜒𝜒 𝑗𝑗 is j-th possible value in X, K indicates the number of levels present in an image, and S stands for intensity sequence number, which is related to the format of the image.Table 3 shows the entropy values for encrypted test images of the encryption scheme. The entropy value measured in this study is marginally different from the value expected by theory.…”
Section: Number Of Pixel Change Rate(npcr) and Unified Average Changi...mentioning
confidence: 99%
See 2 more Smart Citations
“…This table shows that compared to systems employed in past studies, the NPCR and UACI values of the suggested systems in this paper are considered good values to avoid UACI and NPCR attacks and have a better image transmission that is more efficient and safer. (12) 𝑃𝑃 𝑟𝑟 (𝑋𝑋 = 𝜒𝜒 𝑗𝑗 ) = 1 𝐼𝐼𝐼𝐼 (13) where X is the original image, Pr(𝜒𝜒 𝑗𝑗 ) 𝑖𝑖𝑖𝑖 𝑒𝑒𝑞𝑞 (13) is the probability of X = 𝜒𝜒 𝑗𝑗 , 𝜒𝜒 𝑗𝑗 is j-th possible value in X, K indicates the number of levels present in an image, and S stands for intensity sequence number, which is related to the format of the image.Table 3 shows the entropy values for encrypted test images of the encryption scheme. The entropy value measured in this study is marginally different from the value expected by theory.…”
Section: Number Of Pixel Change Rate(npcr) and Unified Average Changi...mentioning
confidence: 99%
“…In addition to being easy to install, it has exceptional resistance to the effects of multipath fading. Fast Fourier Transforms, Discrete Wavelet Transforms, and Discrete Cosine Transforms were all reported in prior research and can be used to construct this method [12][13][14]. Several wireless communication systems and devices, including 4G LTE generation mobile technologies, have incorporated OFDM technology [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IoT applications can be categorized into two groups: low data rate applications like smart meters and high data rate applications like multimedia IoT. A number of IoT communication protocols, including NB-IoT and 802.11 ah, rely on OFDM as an effective multiple access approach to support the successful operation of high data rate IoT applications [ 40 ]. One key feature of IoT systems is their ability to support a variety of legacy and emerging communication protocols, including SigFox, cellular technology, 6LoWPAN (IPv6 Low-power Wireless Personal Area Networks (LoWPAN)), BLE (Bluetooth low energy), ZigBee, RFID (radio frequency identification), NFC (near-field communication), Z-Wave, NB-IoT (Narrow Band IoT), LoRaWAN (long-range wide area network), and Wi-SUN (wireless smart utility network) [ 41 ].…”
Section: Introductionmentioning
confidence: 99%